Fundamentals of environmental sampling and analysis - Zhang, Chunlong (Hoboken: JW-Wiley, 2024)
"The environment includes the non-living (abiotic) and living (biotic) elements that humans interact with and have effects on. The abiotic elements include air, water, and soil, whereas the biotic elements include living things such as plants and animals. Depending on the specific project, such as regulatory enforcement, regulatory compliance, routine monitoring, emergency response, and scientific research, the objectives of environmental sampling and analysis are as follows: 1. To determine how much pollutant enters an environment through stack emission, wastewater discharge, waste disposal, etc. in order to comply with a regulatory requirement. 2. To measure ambient environmental concentrations of analytes, assess the degree of pollution, and to identify short- and long-term trends. 3. To detect accidental releases and evaluate the risk and toxicity to humans and biota. 4. To study the fate and transport of contaminants and to evaluate the efficiency of pollution control and remediation systems"--
Introduction to Environmental Data Acquisition -- Basics of Analytical and Organic Chemistry -- Basics of Environmental Data Validation and Analysis -- Environmental Sampling Design -- Environmental Sampling Techniques -- Methodology and Quality Assurance / Quality Control of Environmental -- Analysis -- Wet Chemical and Field Methods for Common Environmental Parameters -- Fundamentals of Sample Preparation for Environmental Analysis -- Molecular Spectroscopic Methods in Environmental Analysis -- Atomic Spectroscopy for Metal Analysis -- Chromatographic Methods for Environmental Analysis -- Electrochemical Methods for Environmental Analysis -- Mass Spectrometry in Environmental Analysis -- Other Instrumental Methods in Environmental Analysis
Includes bibliographical references and index.
Keywords: Environmental sampling; Environmental sciences -- Statistical methods